2016
DOI: 10.1155/2016/5391682
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal and Postweaning Linseed Dietary Supplementation on Growth Rate, Lipid Profile, and Meat Quality Traits of Light Sarda Lambs

Abstract: The effects of dietary extruded linseed (EL) on growth performance, meat quality, and lipid profile of Semimembranosus and Longissimus lumborum muscles of 81 Sarda lambs were studied in a 3 × 3 design: EL content (0%, 10%, and 20%) of maternal dietary concentrate fed from 20 d to parturition to 60 d of lactation and EL content (0%, 10%, 20%) of lamb concentrate fed after weaning for 30 d. The basal diet was composed of alfalfa and meadow hay during pregnancy and alfalfa hay during lactation. At slaughter, carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…There is information that shows that through the feeding of animals, the content of the different fatty acids present in the meat can be modified [2], altering the proportions between them, to make meat healthier, also with effects on aroma, taste and preservation [2,3,[20][21][22]. This coincides with the results that we have obtained, taking into account the important circumstance that in our trial, diets were not fed directly to lambs but to their mothers during the last third of gestation and during lactation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is information that shows that through the feeding of animals, the content of the different fatty acids present in the meat can be modified [2], altering the proportions between them, to make meat healthier, also with effects on aroma, taste and preservation [2,3,[20][21][22]. This coincides with the results that we have obtained, taking into account the important circumstance that in our trial, diets were not fed directly to lambs but to their mothers during the last third of gestation and during lactation.…”
Section: Discussionmentioning
confidence: 99%
“…This coincides with the results that we have obtained, taking into account the important circumstance that in our trial, diets were not fed directly to lambs but to their mothers during the last third of gestation and during lactation. Although in some experiments it is claimed that animal behavior, lamb yield and carcass traits were not affected by the diet composition of ewes [15,22], Ponnampalam et al (2002) [3] and Gallardo Garcia et al (2013) [1] asserted that changes in the fatty acid profile present in the milk fat produced by ewes could bring about changes in the characteristics and composition of the fat of the carcass of their lambs, offering the possibility to improve their quality, both from a nutritional and functional point of view.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with Kholif et al (2015) who explained that the anaerobic fermentation of oil (as linseed oil) was more efficient and faster in yielding more VFA's than control by indirect way. Enhancing milk amount with oil consumption in G2 and G3 attributed to high α-linolenic acid (ALA) in rations were able to upregulate the peroxisome proliferatoractivated receptors (PPAR-α) gene and downregulate the stearoyl-CoA-desaturase gene compared to control diets with low ALA content (Trabalza-Marinucci et al, 2016). According to Lerma-Reyes et al (2018), they found that oil supplementation could prevent the negative energy balance which has amelioration changes in milk production, then changes in milk production have been observed with higher levels of lipids in diets.…”
Section: Offspring Parametersmentioning
confidence: 99%
“…In addition, it has been demonstrated that the modification of the kids' body size would be a proper response to changing factors such as availability of suckling milk amount (Gallardo et al, 2015). In a sequence of animal studies, offspring and suckled lambs of maternal fed a diet high in calories before birth had heavier body weight throughout life (Trabalza-Marinucci et al, 2016). In a study conducted with dairy Zaraibi goats received oils can able to alter body weight of kids as a result of suckling milk yield (Khalifa et al, 2016).…”
Section: Changing Of Kids Weight From Birth To Weaningmentioning
confidence: 99%
“…Similar to these results, Urrutia et al (2015) indicate that the addition of flax and chia seeds to the meal of lambs can be a useful nutritional strategy for increasing total n-3 polyunsaturated fatty acids (PUFA) and α-linolenic acid (n-3 C18:3), potentially beneficial for human health, as well as for decreasing the values of the ratios of n-6/n-3 PUFA in the meat of lambs. Flax seeds in the nutrition of lambs can effi-ciently affect the modification of fatty acid content and increase the quantity of nutritively active fatty acids in lamb meat (Trabalza-Marinucci et al 2016). Feeding with extruded flax during the weaning period leads to an increase in ALA and long-chain n-3 PUFA in the muscle and fatty tissue of lambs from intensive breeding (Berthelot et al 2012).…”
Section: Introductionmentioning
confidence: 99%